PENGARUH QUALITY OF WORK LIFE (QWL) DAN IKLIM ORGANISASI TERHADAP KINERJA GURU DI SEKOLAH DASAR GLOBAL PRESTASI SCHOOL BEKASI BARAT - rasFadilla (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
Abstract: The objective of the research is finding out the effect of quality of work and organizational climate on the teacher’s employee performance. The research was conducted at Global Prestasi School in North Bekasi. The research was using a survey method with path analysis applied in the hypothesis and 100 respondents. The research techniques are analysis with quantitative research approaches by using causal analysis. The finding of the research is: 1) there is a positive direct effect of quality of work life on employee performance; 2) there is a positive direct effect of organizational climate on employee performance; 3) there is a positive direct effect of quality of work life on organizational climate. Result the of the research show that quality of work life and organizational climate has impact to job performance with sign = 0,000 or sig < 0,05